Preliminary neutronic study of the S-PRISM fast reactor - João Manoel Losada Moreira (Brazilian Journal of Radiation Sciences, 2021)
Waste management is a challenge currently faced by nuclear energy worldwide. Most nuclear power plants operate in a once-through cycle and all spent nuclear fuel is stored in long term. Fast reactors can recycle 96% of the material in spent nuclear fuel of thermal reactors, reducing drastically the time required to store the waste. The S-PRISM reactor is a modular, pool-type sodium-cooled fast reactor that can operate with a variety of fuel types. In this study, the advantages presented by fast reactors were briefly discussed and a preliminary analysis of the fuel pin cells was made. It was found that the isothermal coefficient of reactivity was lower than a regular PWR's, with neutron leakage playing a major role instead of coolant or doppler expansion. The k∞ showed decrease for the driver pin and increase for the blanket pin during burnup; opposite behavior was observed for the conversion ratio. No results for pin analysis were found in literature for comparison. As the simulations were carried out separately instead of in a system, the results are not representative of the whole core behavior but must be seen as a path to understand the different types of pin influence in the system.